Eighteenth century English labouring-class poets, 1700-1800 - Goodridge, John (Pickering & Chatto, 2003)
Poets of labouring class origin were published in Britain in the 18th and 19th centuries. Some were popular and important in their day but few are available today. This is a collection of some of those poems from the 18th century.